Species and Size Composition of Seahorses (Genus Hippocampus, Family Syngnathidae) in the Coastal Waters and Local Market of Kota Kinabalu, Sabah, Malaysia - Rossita Shapawi,; Adrian Leslie Anyie,; Muhammad Ali Syed Hussien,; Wahidatul Husna Zuldin, (Tropical Life Sciences Research, 2015)
Seahorse diversity (genus Hippocampus, Family Syngnathidae), species identification, size composition and sexual dimorphism were studied from November 2012 to March 2013 in selected coastal waters around Kota Kinabalu, Sabah and the local market trade. Six species of seahorses were identified in the study: (1) Hippocampus barbouri, (2) Hippocampus comes, (3) Hippocampus kelloggi, (4) Hippocampus kuda, (5) Hippocampus spinosissimus and (6) Hippocampus trimaculatus. All six species were sold at the local market, and the dried seahorses were obtained mainly by local fishermen using trawl by-catch method and traded as traditional medicine, souvenirs and other uses. Four species were identified by direct samplings in various different habitats of Kota Kinabalu coastal waters: (1) H. barbouri, (2) H. comes, (3) H. kuda, and (4) H. spinosissimus. Based on the results, H. comes was the largest in size among the four fresh/live species found (mean standard length [SL]: 148.25±1.26 mm), whereas H. barbouri was the smallest species (mean SL: 129±7.81 mm). For the dried samples, H. kelloggi was the largest (mean SL: 245.25±14.55 mm) and H. barbouri was the smallest (mean SL: 127.21±10.01 mm). No significant difference (p>0.05) was observed between the lengths of males and females in every seahorse species, and there was no sexual size dimorphism in any of the species. The findings from the study are significant to provide baseline data for the conservation efforts of these unique marine teleost. Kepelbagaian kuda laut (genus Hippocampus, Famili Syngnathidae), komposisi saiz dan perbezaan saiz berdasarkan jantina telah dikaji pada bulan November 2012 sehingga Mac 2013 di kawasan-kawasan terpilih sekitar perairan dan pasar tempatan di Kota Kinabalu, Sabah. Sebanyak enam spesies kuda laut telah dikenal pasti melalui kajian ini iaitu: (1) Hippocampus barbouri, (2) Hippocampus comes, (3) Hippocampus kelloggi, (4) Hippocampus kuda, (5) Hippocampus spinosissimus dan (6) Hippocampus trimaculatus. Kesemua enam spesies dijual di pasaran tempatan dan didapati bahawa kebanyakan kuda laut kering adalah hasil daripada tangkapan pukat tunda dan didagangkan sebagai ubat tradisional, cenderamata dan untuk kegunaan lain. Sebanyak empat spesies iaitu (1) H. barbouri, (2) H. comes, (3) H. kuda dan (4) H. spinosissimus telah ditemui menggunakan kaedah penyampelan secara terus di habitat yang berbeza sekitar perairan Kota Kinabalu. H. comes adalah yang terbesar dalam kalangan empat spesies hidup yang ditemui (min standard length [SL]: 148.25±1.26 mm), manakala H. barbouri adalah yang paling kecil (min SL: 129±7.81 mm). Bagi sampel kering, H. kelloggi adalah yang terbesar (min SL: 245.25±14.55 mm) dan H. barbouri adalah yang terkecil (min SL: 127.21±10.01 mm). Tiada perbezaan ketara (p>0.05) antara panjang jantan dan betina serta tiada perbezaan saiz berdasarkan jantina dalam setiap spesies. Sebagai kesimpulan, hasil kajian ini adalah penting bagi memberikan beberapa data asas dalam usaha pemuliharaan teleost marin yang unik ini.